ผลกระทบของเขม่าดำต่อเสถียรภาพในการผลิตยางคอมพาวด์ - วริษฐา ศักดิ์สิทธิ์พรชัย (จุฬาลงกรณ์มหาวิทยาลัย, 2019)
This study attempted to correlate the effect of carbon black properties on rubber compound properties from production (e.g. modulus, hysteresis, curing time). Carbon black can be divided into various grades. This project focused on carbon black grades N234 and N550 which have different structures, sizes and reactive surfaces. The technique of measuring oil absorption number on carbon black surface was the main method to access its and reactive surface. Under the time period of this study, no obvious trend of effect of carbon black on rubber compound properties production was found. The traceability study of carbon black used in production could yield the alert specification of oil absorption number of grade N550 carbon black at 115 and 123 mL/100g. When the carbon black was specifically controlled in the production, the oil absorption numbers of N234 carbon black were found to correlate directly to modulus of the rubber compound, while reversely to hysteresis and curing time. However, N550 carbon black showed direct correlations of oil absorption number with modulus and hysteresis of rubber compound.